Readjustment of antithrombotic therapy in stroke-patients owing to transesophageal echocardiography findings - Bruening, Toralf; Al-Khaled, Mohamed (Journal of Cardiology and Cardiovascular Medicine, 2019)
Objectives: Cardioembolic etiology is a frequent source of ischemic stroke. Echocardiogram is the mainstay of cardioembolic source detection with regard to plan secondary stroke management, however it remains unclear how often clinically actionable findings are provided hereby. In addition, it is uncertain whether echocardiography should be performed transthoracic or transesophageal (TEE). In a monocenter study, we evaluated the frequency of pathological findings from TEE evaluation in patients with ischemic stroke with suspected cardioembolic and cryptogenic source and determined whether there was an associated adjustment in the prescribed administration of antithrombotic therapy. Materials and Methods: Over a 21-month period (2012-2013), we enrolled 143 patients in a prospective monocenter study (mean age ± standard deviation, 70 ± 12 years; females, 44.1%) who were admitted to the Department of Neurology at the University of Lübeck due to ischemic stroke and who underwent TEE due to supposed cardiac embolism. We assessed the presence of atrial fibrillation; days from admission to TEE; and TEE findings, including atrial septal aneurysm, thrombogenic aortic arch, valve failure, presence of left atrial thrombus, and patent foramen ovale. Demografic information and medical history were drawn from patient records and the hospital information system. Results: On average, TEE was performed 4 days after admission to the hospital. Left atrial thrombus was detected in 3 patients (2.1%), patent foramen ovale (PFO) in 27 (18.9%), atrial septum aneurysm in 17 (11.9%), and thrombogenic aortic arch in 29 (20.3%). Findings from TEE were commonly associated with therapeutic adjustment; antiplatelet therapy increased from 30.1% to 80.4%, oral anticoagulation therapy increased from 2.8% to 27.3%. Conclusion: Findings from TEE for the evaluation of ischemic stroke lead to frequent adjustment of prior antithrombotic therapy, antiplatelet as well as anticoagulation.